GE_GERICHTE P/7268/2023 vom 9. Mai 2025 - GE Cour de justice (2025)
VIOLENCE DOMESTIQUE;VIOL;ENLÈVEMENT(INFRACTION);MENACE(DROIT PÉNAL);CONTRAINTE(DROIT PÉNAL);EXPULSION(DROIT PÉNAL);TORT MORAL | CP.190; CP.180; CP.181; CP.123; CP.126; CP.66.al2; CO.49